The Role of Elders in the Wellbeing of a Contemporary Australian Indigenous Community. (30th November 2018) - Busija, Lucy; Cinelli, Renata; Toombs, Maree R; Easton, Caitlin; Hampton, Ron; Holdsworth, Kristen; Macleod, BPsySc(Hons), Ashley; Nicholson, Geoffrey C; Nasir, Bushra F; Sanders, Kerrie M; McCabe, Marita P
Abstract: Background and Objectives: Traditional Elders are integral to the social structure of Australian Indigenous communities. Due to progressive loss of traditional way of life, however, the role of Elders has been eroding. This study aims to develop a conceptual model of the role of Elders in an Australian Indigenous community, with the goal of attaining strategies to strengthen the role of Elders. Research Design and Methods: The study, conducted in a regional Indigenous community in Australia, adopted a community-based participatory approach. Design and focus of the project were informed by a community forum (Yarning Circle). One-on-one semistructured interviews and focus groups with community members were conducted by Indigenous researchers. Group concept mapping (GCM) was applied to elicit major themes in qualitative data, from the point of view of community members, and to derive a conceptual model of the role of Elders. Results: Fifty members of the Indigenous community took part in interviews and focus groups. The participants' median age was 45 years (range 18–76 years); 31 (62%) were female. An additional 24 Indigenous community members took part in the data sorting task of GCM. GCM identified seven major aspects of the role of Elders, including Community relations, Passing down the knowledge, Dealing with racism and oppression, Building a better resourced community, Intergenerational connectedness, Safeguarding our identity, and Caring for our youth . Discussion and Implications: Elders fulfill many important roles in contemporary Indigenous communities. Our results can be used to assist the community to codesign a program to increase community wellbeing.